2017
DOI: 10.1007/s12026-017-8980-5
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune/inflammatory syndrome induced by adjuvants—ASIA—related to biomaterials: analysis of 45 cases and comprehensive review of the literature

Abstract: Systemic autoimmune or granulomatous disorders related to biomaterials of human use have rarely been described. The aim of this study was to report cases of autoimmune/inflammatory syndrome induced by adjuvants (ASIA) related to biomaterial injections and prostheses, mainly silicone, hyaluronic acid, acrylamides and methacrylate compounds in a Spanish patient cohort. This study is a retrospective analysis of clinical, laboratory, histopathological and follow-up data of 45 cases of patients suffering from late-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
75
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(77 citation statements)
references
References 147 publications
1
75
0
1
Order By: Relevance
“…Alijotas-Reig et al observed that 15 out of 185 cases (8%) of patients suffering from inflammatory/autoimmune disorders related to bioimplant injections had systemic or distant and multiple complaints that could be categorized as ASIA. SS was diagnosed in two patients representing a rather infrequent yet possible manifestation following a chronic stimulation from biomaterials used as fillers [ 89 ], an evidence reinforced by a further 3 cases published later on [ 90 ]. Thus, the epidemiology and pathomechanisms possibly linking some agents acting as adjuvants such as vaccines, silica, silicone implants and other biomaterials with SS are yet to be clarified.…”
Section: Classical Examples Of the Asia Syndromementioning
confidence: 99%
“…Alijotas-Reig et al observed that 15 out of 185 cases (8%) of patients suffering from inflammatory/autoimmune disorders related to bioimplant injections had systemic or distant and multiple complaints that could be categorized as ASIA. SS was diagnosed in two patients representing a rather infrequent yet possible manifestation following a chronic stimulation from biomaterials used as fillers [ 89 ], an evidence reinforced by a further 3 cases published later on [ 90 ]. Thus, the epidemiology and pathomechanisms possibly linking some agents acting as adjuvants such as vaccines, silica, silicone implants and other biomaterials with SS are yet to be clarified.…”
Section: Classical Examples Of the Asia Syndromementioning
confidence: 99%
“…There may be some debate as to whether any silicone-related reaction is always an acquired entity or whether some may have crossreactive or direct immune reactions that are stimulated after non-specific polyclonal activation for other reasons. Whereas silicone has drawn much attention in the ASIA context, various non-silicone adjuvants have also been associated with similar immune activations [61][62][63][64][65][66][67][68]. These include in the least acrylates, hyaluronic acid derivatives, acrylamides, poly-L-lactic acid, dental amalgams, various skin fillers, and vaccine components.…”
Section: Autoimmune/inflammatory Syndrome Induced By Adjuvantsmentioning
confidence: 99%
“…Even more open is the mechanism in which autoimmunity can be triggered by foreign adjuvants [6,68,70]. Adjuvancy per se conceivably utilizes various pathways, whether innate or adaptive.…”
Section: Autoimmune/inflammatory Syndrome Induced By Adjuvantsmentioning
confidence: 99%
“…Recent publications have described two patient series suspected of having ASIA associated with implanted medical devices including silicone breast implants, skin fillers, and metal implants. Alijotas-Reig et al (Alijotas-Reig et al, 2018) performed a retrospective analysis of 45 subjects and reported a 6year average latency from implantation to symptoms. Eighty percent (80%) of these subjects tested positive for the production of antinuclear antibody (ANA), a biomarker often associated with connective tissue autoimmune disorders.…”
Section: Clinical Characteristicsmentioning
confidence: 99%